Perspektif Sosiologis-Teologis terhadap Interaksi Sosial Antara Etnis Rote dan Etnis Timor di Desa Tuasene Kecamatan Mollo Selatan Kabupaten Timor Tengah Selatan - Daud Alfons Pandie; Remegises Danial Yohanis Pandie (REAL DIDACHE: Journal of Christian Education, 2023)
This paper aims to describe the social and cultural construction in the process of interaction between the Rote ethnicity and the Timorese ethnicity in Tuasene Village, South Mollo district, South Central Timor Regency. Where, the dynamics in the process of interaction of ethnic Rote and Ethnic Timorese are different customs and cultures, so that the social construction in the village of Tuassene is dominated by ethnic Rote. This paper draws on the theoretical framework of social constructions of Peter L. Berger and Thomas Lukmann, this paper focuses on the social constructions that arise in such interactions. As Berger puts it, humans create reality through social interaction. In this study the researcher found that the social interaction of the Rote ethnicity and the Timorese ethnicity in the village of Tuasene from a theological perspective was part of God's will for humans to live in harmony and peace which then influenced the construction of the Rote ethnic social and cultural identity in Tuasene, although it lasted for a long time and time. Such social interactions form the construction of ethnic and cultural identities is a synthesis of those processes of social interaction.Keywords: ethnic; Perspective; social construction; Rote; Sociological; Theological; TimorAbstrakTulisan ini bertujuan untuk mendeskripsikan konstruksi sosial dan budaya dalam proses interaksi antara etnis Rote dengan Etnis Timor di Desa Tuasene, kecamatan Mollo Selatan, Kabupaten Timor Tengah Selatan. Di mana, dinamika dalam proses interaksi etnis Rote dan Etnis Timor yang berbeda adat istiadat serta kebudayaan, sehingga konstruksi sosial di desa Tuassene di dominasi oleh etnis Rote. Tulisan ini mengacu pada kerangka teoritis konstruksi sosial Peter L. Berger dan Thomas Lukmann, tulisan ini berfokus pada konstruksi sosial yang muncul dalam interaksi tersebut. Sebagaimana dikatakan oleh Berger, manusia menciptakan realitas melalui interaksi sosial. Dalam penelitian ini peneliti menemukan bahwa interaksi sosial etnis Rote dan etnis Timor di desa Tuasene dari perspektif teologis merupakan bagian dari kehendak Tuhan agar manusia hidup dengan rukun dan damai yang kemudian mempengaruhi konstruksi identitas sosial dan budaya etnis Rote di Tuasene, meskipun berlangsung dalam proses dan waktu yang cukup lama. Interaksi sosial tersebut membentuk konstruksi identitas etnis dan budaya merupakan sintesis dari proses interaksi sosial tersebut.Kata Kunci: etnis; perspektif; konstruksi sosial; rote; sosiologis; teologis; timor